Narrative Review: Edible Film Strip Antioksidan dari Ekstrak Herba Kelingkit (Malpighia coccigera L.) - Nur Hidayah Saputri; Febby Oliviary Derajathun; Yuni Fadilah Husain; Selpirahmawati Saranani (Ikatan Senat Mahasiswa Farmasi Seluruh Indonesia, 2021)
Introduction: Edible Film Strip (EFS) is one of pharmaceutical preparations that could be formulated with active antioxidant ingredient from dwarf holly/kelingkit (Malphigia coccigera L). The aim of this narrative review is to narrate the article summary of the exploration outcome regarding the potential antioxidant from the extraction of dwarf holly/kelingkit in the form of EFS. Methods: This narrative review conducted the method of literature review or the secondary data compilation from several scientific journals and antioxidant activity testing from DPPH and ABTS methods as well as the EFS formulation. Result: Malpighia contains phenolic compounds in having antioxidant activity with its ability to capture an neutralize free radicals. Conclusion: The extraction of antioxidant in the EFS dosage form has the potential for the immune system and prevent degenerative diseases.